A case based human reliability assessment using HFACS for complex space operations. Issue 1 (March 2019) - Alexander, Tiffaney Miller
Abstract: Multiple studies have shown that more than half of aviation, aerospace and aeronautics incidents are attributed to human error. Although many existing incident report systems have been beneficial for identifying engineering failures, most of them are not designed around a theoretical framework of human error, thus failing to address core issues and causes of the mishaps. In addition, the collection and classification of human error data can be a challenge, including the causal factors that impact human behavior. Therefore, it is imperative to develop a human error assessment framework to identify these causes[1] . The objective of this article is to provide a high-level literature overview and comparison of relevant human error assessment methods and provide an example of how one of these tools can be used to perform a human error analysis for complex space operations. The Human Factors Analysis and Classification System (HFACS) is one tool that can be used to categorize human error causal factors in a Space Operations environment. Due to the uniqueness of Space Operations and its complexity, there are very limited Human Reliability Assessment (HRA) tools specifically established for identifying and assessing human error. It is recommended that further research be done to fill the gap of HRAs, as it applies specifically to Ground Processing Operations.